2017
DOI: 10.1016/j.orgel.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relative humidity and temperature on the stability of DNTT transistors: A density of states investigation

Abstract: Exposure to moisture and elevated temperatures usually results in significant degradation of organic thin film transistor (OTFT) performance. Typical observations include reduced mobility, unstable threshold voltage and the appearance of hysteresis in electrical characteristics. In this contribution we investigate the effects of environmental conditions on OTFTs based on DNTT, a high-mobility, small-molecule, organic semiconductor, with polystyrene (PS) as the gate insulator. Device characteristics were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The characteristic decay of the trap DOS into the band gap is in agreement with other reports on vacuum‐deposited films of the organic semiconductor DNTT. [ 40,41 ] The results in Figure 3b show a clear correlation between the surface roughness of the gate dielectric and the density of trap states in the organic semiconductor layer. Figure illustrates the general view of how the roughness of the underlying surface (in this case of the gate dielectric) affects the growth and morphology of the organic semiconductor layer by increasing the degree of structural disorder.…”
Section: Resultsmentioning
confidence: 94%
“…The characteristic decay of the trap DOS into the band gap is in agreement with other reports on vacuum‐deposited films of the organic semiconductor DNTT. [ 40,41 ] The results in Figure 3b show a clear correlation between the surface roughness of the gate dielectric and the density of trap states in the organic semiconductor layer. Figure illustrates the general view of how the roughness of the underlying surface (in this case of the gate dielectric) affects the growth and morphology of the organic semiconductor layer by increasing the degree of structural disorder.…”
Section: Resultsmentioning
confidence: 94%
“…In previous reports on environmental [24] and bias stress [25] Liguori et al [22] identify excellent light sensitivity and high mobility as the key factors in achieving a high optical response in OTFTs. The latter is confirmed in the review by Baeg et al [7] in which four out of the five highest responsivities reported (10 3 to 10 4…”
Section: Discussionmentioning
confidence: 99%
“…This initial fast response is followed by a slower response from slow hole trapping and/or electron de-trapping, which is not complete during the 100 s period in the dark. The As a final check that the effects we observe are related to interface states, we used the Grünewald model [24,25,35,38] Information show that, an apparent increase in the concentration of deeper states is independent of both the intensity and duration of the illumination, especially following 460 nm illumination. These features are unlikely, therefore, to be associated with bulk state creation in the DNTT.…”
Section: Stress Conditionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, small molecule semiconductors have got attention for OTFTs, for example dinaphtho[2,3-b:2',3'-f] thieno[3,2-b]thiophene (DNTT) exhibits higher stability than pentacene and P3HT. In addition, extra oxygen-doping enables relatively high mobility [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%